Tigo Luhah Tanah Sekudung Customary Criminal Law as a Mirror of Local Wisdom: The Survival of Traditional Values in the Midst of Modernity - Zahara, Mina; Hadi , Samsu (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
Tigo Luhah Tanah Sekudung Customary Criminal Law is a form of traditional legal system that lives and is practiced by indigenous peoples as a guideline in maintaining social order and harmony of life together. This research aims to analyze the customary criminal law as a mirror of local wisdom and examine the survival of traditional values in the midst of the ever-growing currents of modernity. This research uses a qualitative method with a cultural approach, which places customary law as a cultural product full of meaning, values, symbols, and social norms. Data collection techniques are carried out through participatory observation, in-depth interviews with indigenous leaders, stakeholders, and local communities, as well as documentation studies of customary texts and applicable legal practices. The results of the study show that the Tigo Luhah Tanah Sekudung Customary Criminal Law not only functions as an instrument for conflict resolution, but also as a means of inheriting moral values, restorative justice, and social solidarity. Despite facing the challenges of modernization and the state's formal legal system, this customary criminal law survives through a process of adaptation, compromise, and strong social legitimacy in society. This resistance emphasizes that local wisdom has a strategic role in maintaining cultural identity and providing alternative contributions to the development of justice and rooted in local values. Abstrak. Hukum Pidana Adat Tigo Luhah Tanah Sekudung merupakan salah satu bentuk sistem hukum tradisional yang hidup dan dipraktikkan oleh masyarakat adat sebagai pedoman dalam menjaga keteraturan sosial dan harmoni kehidupan bersama. Penelitian ini bertujuan untuk menganalisis hukum pidana adat tersebut sebagai cermin kearifan lokal serta menelaah kebertahanan nilai-nilai tradisional di tengah arus modernisasi yang terus berkembang. Penelitian ini menggunakan metode kualitatif dengan pendekatan budaya, yang menempatkan hukum adat sebagai produk budaya yang sarat makna, nilai, simbol, dan norma sosial. Teknik pengumpulan data dilakukan melalui observasi partisipatif, wawancara mendalam dengan tokoh adat, pemangku kepentingan, dan masyarakat setempat, serta studi dokumentasi terhadap naskah adat dan praktik hukum yang berlaku. Hasil penelitian menunjukkan bahwa Hukum Pidana Adat Tigo Luhah Tanah Sekudung tidak hanya berfungsi sebagai instrumen penyelesaian konflik, tetapi juga sebagai sarana pewarisan nilai-nilai moral, keadilan restoratif, dan solidaritas sosial. Meskipun menghadapi tantangan modernisasi dan sistem hukum formal negara, hukum pidana adat ini tetap bertahan melalui proses adaptasi, kompromi, dan legitimasi sosial yang kuat dalam masyarakat. Kebertahanan tersebut menegaskan bahwa kearifan lokal memiliki peran strategis dalam menjaga identitas budaya serta memberikan kontribusi alternatif dalam pembangunan hukum yang berkeadilan dan berakar pada nilai-nilai lokal.